Learning by Adoption: The International Adoption Experience of Canadian and Dutch Adoptive Parents of Children from the United States - Dana Naughton (Adult Education Research Conference, 2014)
This paper explores the international adoption experience of Dutch and Canadian adopters of U.S. born children through the lens of adult learning, adult education and lifelong learning.